Reconstruction of Memory and Memorials in Szıgetvár - Peker, Ali Uzay (ICONARCH International Congress of Architecture and Planning, 2017)
Recent discovery of the Tomb of Sultan Suleiman within a palanka (redoubt) close to the town of Szigetvár proved to be a worldwide archaeological event with unexpected repercussions. The Tomb of Suleiman has been a major source of scholarly and public interest, but the central role of the historic town of Szigetvár has also become highlighted. In 1566, Sultan Suleiman went to the location for the reason to take Szigetvár and died in his royal tent close to the town one night before the downfall of it. They shared a common fate: Sultan and the Christian town have gone. Later a tomb and its adjacent buildings were erected on the site commemorating Sultan’s death. Szigetvár now became a typical Ottoman Turkish-Islamic town, which lived as such for a century and a few decades more. Its capture by the Christian forces and destruction of the entire Ottoman-Turkish urban fabric together with the Sultan’s tomb introduced a similar faith. Now the Christian town is refurbished in the place of the Muslim town. In point of fact history of Szigetvár is a history of construction and reconstruction of memory. Memories become concretized with memorials, which become reconstructed to make room for new memories and memorials. The site of the Sultan’s tomb, old fortress and modern town are dotted by such reminders and new ones are being built today. Szigetvár is a palimpsest of permutations that is the real source of its heritage value. The paragon of the town is reconstruction of memories and memorials. In this paper, we draw a map of historical relocations also in Hungary in order to point out a cycle of memory reconstruction with the aim to help accommodate the Ottoman case.